Exploring Marketing Information Systems (MkIS) selection and evaluation criteria: implications for suppliers. (29th February 2008) - Andronikidis, Andreas; Vassiliadis, Christos; Fotiadis, Thomas; Priporas, Constantinos-Vasilios
This paper reports the findings of a research that incorporated two phases ? before and after ? the acquisition of the Marketing Information System (MkIS) product. An extensive account of the criteria in the selection and evaluation process used by a sample of Greek manufacturing companies is given to illustrate perceived benefits and critical points for suppliers. In the first phase, three main categories of criteria, namely, supplier's name and reputation, financial terms of acquisition and customer support service, were identified as elements that influence choice decisions. For triangulation purposes, a questionnaire was designed based on the qualitative results and distributed to companies in the first phase. Factor analysis validated the results provided by the qualitative exploration. In the second phase, data collected through the same questionnaire survey were employed to evaluate the findings. Results suggest that the importance placed by companies on the customer support service factor increases, while the emphasis on the cost factor diminishes.